High-strength and high-toughness hypoeutectic aluminum-silicon alloy and preparation method thereof

By adding SR and ZR elements to aluminum and silicon alloys, and two deterioration treatment and rapid temperature and cooling heat treatment, the micro -tissue of the alloy is optimized, solving the problem of insufficient performance of the Asian crypt crystal aluminum alloy, significantly improves its strength , Toughness and extension.

CN119351834APending Publication Date: 2025-01-24KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466309.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The comprehensive performance of the existing subeutectic aluminum-silicon alloys is insufficient, which leads to poor performance in higher demands application scenarios. The primary α(Al) dendrites are coarse and unevenly distributed, which affects the strength of the alloy. and resilience.

Method used

By adding SR and ZR elements to aluminum and silicon alloy, and two deterioration treatment, the combination of rapid heating up and cooling heat treatment in the combination of the micro -tissue of the alloy, making the common crystal SI phase short rod and ballization, forming a fine common common commonly commonly used together Crystal group.

Benefits of technology

It significantly improves the strength, toughness and elongation of aluminum-silicon alloy, enhances its comprehensive mechanical properties, and enables it to meet a wider range of application requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351834A_ABST
    Figure CN119351834A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-toughness hypoeutectic aluminum-silicon alloy and a preparation method thereof, and belongs to the technical field of aluminum-silicon alloys. The hypoeutectic aluminum-silicon alloy disclosed by the invention is prepared from the following components in percentage by mass: 9.2 to 9.8 percent of Si, 0.1 to 0.3 percent of Zr, 0.1 to 0.2 percent of Fe, 0.01 to 0.02 percent of Sr, 0.01 to 0.02 percent of Mg and the balance of Al and inevitable impurity elements. The preparation method comprises the following steps: (1) preheating a smelting furnace, and carrying out primary modification treatment; (2) carrying out secondary modification treatment; (3) pouring a metal mold; (4) homogenization treatment; (5) performing staged rapid heating and cooling solution treatment; and (6) aging treatment. The aluminum-silicon alloy with high strength, toughness and ductility can be prepared by carrying out modification treatment on the aluminum-silicon alloy twice and combining the preparation method, and a good foundation is laid for expanding the application range of the aluminum-silicon alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum-silicon alloys, and relates to a high-strength and high-toughness hypoeutectic aluminum-silicon alloy and a preparation method thereof. Background Art

[0002] Aluminum-silicon alloy is lightweight and has high strength. Its good castability and machinability enable it to be processed into general components.

[0003] At present, hypoeutectic Al-Si alloys are mainly used to manufacture castings with low load-bearing capacity and low quality requirements. However, there is still much room for improvement in the comprehensive performance of hypoeutectic Al-Si alloys. After the comprehensive performance is improved, it can be suitable for more application scenarios and expand its application scope, which is of great significance.

[0004] For hypoeutectic aluminum-silicon alloys, their performance is mainly affected by the primary crystal, eutectic microstructure and eutectic (cluster) grains. Since the Si content in Al-Si alloys is relatively high, the primary α (Al) dendrites in the cast state are relatively coarse and unevenly distributed, resulting in the hypoeutectic silicon presenting needle-shaped and flake-like morphologies, which has a serious negative impact on the alloy properties.

[0005] Therefore, it is necessary to provide a high-strength and high-toughness hypoeutectic aluminum-silicon alloy and a preparation method thereof. By optimizing the alloy composition and combining the preparation method, the comprehensive performance of the hypoeutectic aluminum-silicon alloy can be improved and its application range can be expanded. Summary of the invention

[0006] In order to overcome the problems in the background technology, the present invention adds Sr and Zr elements to the aluminum-silicon alloy, performs two modification treatments on the aluminum-silicon alloy, and combines staged rapid heating and cooling heat treatment to prepare an aluminum-silicon alloy with improved strength, elongation and toughness, so that the aluminum-silicon alloy can meet a wider range of application requirements.

[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0008] On the one hand, the present invention proposes a high-strength and high-toughness hypoeutectic aluminum-silicon alloy, which includes, by mass fraction, Si: 9.2-9.8%, Zr: 0.1-0.3%, Fe: 0.1-0.2%, Sr: 0.01-0.02%, Mg: 0.01-0.02%, and the remainder is Al and unavoidable impurity elements.

[0009] Another aspect of the present invention provides a method for preparing the above-mentioned high-strength and high-toughness hypoeutectic aluminum-silicon alloy.

[0010] The preparation method comprises the following steps:

[0011] (1) After the furnace is preheated, single-element Sr and Al-Si master alloy are added according to the mass fraction, and the temperature is continuously raised to perform a modification treatment on the Al-Si master alloy;

[0012] (2) keeping the heating temperature in step (1) unchanged, adding Al-Zr master alloy to the alloy after the primary modification treatment in step (1), adding a refining agent and stirring the molten metal liquid, and performing a secondary modification treatment;

[0013] (3) pouring the molten metal after the secondary modification treatment in step (2) into a metal mold to obtain an alloy sample;

[0014] (4) performing a homogenization heat treatment on the alloy sample obtained in step (3), and then air-cooling the alloy sample to room temperature to obtain an alloy blank;

[0015] (5) subjecting the alloy blank obtained in step (4) to a rapid heating and cooling solid solution treatment in stages to obtain an alloy sample;

[0016] (6) performing an aging treatment on the alloy sample obtained in step (5), and then air-cooling it to room temperature to obtain a high-strength and high-toughness hypoeutectic aluminum-silicon alloy.

[0017] Preferably, in step (1), the furnace is preheated to 550° C. and kept warm for 2 hours.

[0018] Preferably, in the step (1), after adding single substance Sr and Al-Si master alloy, the temperature is raised to 700-720° C. and kept at this temperature for 20-30 minutes to complete a modification treatment.

[0019] Preferably, in the step (2), after adding the Al-Zr master alloy and the refining agent, the mixture is kept warm for 50 to 60 minutes.

[0020] Preferably, in step (2), the refining agent includes potassium chloride (KCl) and sodium fluorosilicate (Na2SiF6).

[0021] Preferably, in step (4), the homogenization heat treatment temperature is 500-550° C., and the holding time is 2 h.

[0022] Preferably, in step (5), the first stage heating rate is 80°C / s, the temperature is raised to 460°C, kept warm for 2 hours, and then water-cooled quenching is performed; the second stage heating rate is 100°C / s, the temperature is raised to 500°C, kept warm for 2 hours, and then water-cooled quenching is performed; the third stage heating rate is 120°C / s, the temperature is raised to 540°C, kept warm for 2 hours, and then water-cooled quenching is performed to obtain an alloy sample.

[0023] Preferably, in step (6), the aging temperature is 160-180° C., and the insulation time is 4-6 hours.

[0024] Preferably, the alloy sample obtained in step (5) is cooled to the aging temperature by air cooling, and then the alloy sample is placed in a heating furnace for heat preservation to complete the aging treatment.

[0025] Beneficial effects of the present invention:

[0026] 1. The present invention performs two modification treatments by first adding Sr element and then adding Zr element, so as to shorten and spheroidize the needle-shaped and flaky Si phases, make the branches of eutectic silicon fine and fibrous, increase the defect density in the crystal, have a higher energy state and a larger energy state non-uniformity, and at the same time make the eutectic Si phase no longer protrude from the growth interface, spheroidize, and grow in coupling with the primary α (Al) to form a small and dense eutectic cluster, thereby effectively improving the comprehensive performance of the aluminum silicon alloy.

[0027] 2. The present invention can better destroy the atomic interaction between the solid solution and the precipitated phase, improve the solid solubility, further strengthen the restriction on the protruding growth interface of the eutectic Si phase, further promote the gradual spheroidization of the eutectic Si phase, thereby promoting the refinement of the eutectic Si phase and further strengthening the comprehensive performance of the aluminum-silicon alloy through staged rapid heating and cooling solution treatment.

[0028] 3. The preparation method of the present invention has strong controllability, a relatively simple process, and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with specific embodiments.

[0031] In the examples and comparative examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure reagents for the experiments.

[0032] Example 1

[0033] The composition of the high-strength and high-toughness hypoeutectic aluminum-silicon alloy of this embodiment is shown in Table 1.

[0034] Table 1

[0035] Si Zr Fe Sr Mg margin 9.8% 0.3% 0.1% 0.02% 0.01% Al and inevitable impurities

[0036] The preparation method of the high-strength and high-toughness hypoeutectic aluminum-silicon alloy described in this embodiment specifically includes the following steps:

[0037] (1) Preheat the crucible furnace to 550℃ and keep it warm for 2h to shorten the subsequent smelting time. According to the composition in Table 1, add the prepared elemental Sr and Al-Si master alloy into the crucible furnace and heat it. Raise the temperature of the crucible furnace to 700℃ and keep it warm for 30min to complete the first modification treatment.

[0038] (2) Keeping the crucible furnace temperature at 700°C, add Al-Zr master alloy and refining agents (KCl) and (Na 2 SiF 6 ), while stirring the molten metal, and after keeping warm for 55 minutes, the secondary modification is completed. Refining agent is added to achieve the purpose of slag removal, and stirring promotes the dissolution of alloy elements.

[0039] (3) The molten alloy liquid after the secondary modification treatment is poured into a metal mold to obtain an alloy sample.

[0040] (4) The alloy sample was subjected to homogenization heat treatment at 500°C and kept at this temperature for 2 h. The alloy sample was then air-cooled to room temperature to obtain an alloy billet.

[0041] (5) The alloy blank is placed in a spark plasma sintering furnace for three stages of rapid heating and cooling heat treatment. In the first stage, the temperature is increased to 460°C at a rate of 80°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s. In the second stage, the temperature is increased to 500°C at a rate of 100°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s. In the third stage, the temperature is increased to 540°C at a rate of 120°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s to obtain an alloy sample.

[0042] (6) The alloy sample was taken out from the plasma sintering furnace, air-cooled to 160°C in air, and then placed in a heating furnace to keep warm for 4 hours. After that, the alloy sample was taken out and air-cooled to room temperature in air to obtain a hypoeutectic aluminum-silicon alloy.

[0043] The aluminum-silicon alloy prepared in this embodiment was subjected to performance tests, and the yield strength of the alloy was measured to be 401.4 MPa, the tensile strength was 482.2 MPa, the elongation was 19.5%, and the average impact energy was 26.4 J.

[0044] Example 2

[0045] The composition of the high-strength and high-toughness hypoeutectic aluminum-silicon alloy of this embodiment is shown in Table 2.

[0046] Table 2

[0047] Si Zr Fe Sr Mg margin 9.5% 0.2% 0.2% 0.01% 0.02% Al and inevitable impurities

[0048] The preparation method of the high-strength and high-toughness hypoeutectic aluminum-silicon alloy described in this embodiment specifically includes the following steps:

[0049] (1) Preheat the crucible furnace to 550℃ and keep it warm for 2h to shorten the subsequent smelting time. According to the composition in Table 2, add the prepared elemental Sr and Al-Si master alloy into the crucible furnace and heat it. Raise the temperature of the crucible furnace to 710℃ and keep it warm for 25min to complete the first modification treatment.

[0050] (2) Keeping the crucible furnace temperature at 710°C, add Al-Zr master alloy and refining agents (KCl) and (Na2SiF6) to the molten metal after the primary modification, stir the molten metal at the same time, and complete the secondary modification after keeping the temperature for 50 minutes. Add the refining agent to achieve the purpose of slag removal, and stir to promote the dissolution of alloy elements.

[0051] (3) The molten alloy liquid after the secondary modification treatment is poured into a metal mold to obtain an alloy sample.

[0052] (4) The alloy sample was subjected to homogenization heat treatment at 525°C and kept at this temperature for 2 h. The alloy sample was then air-cooled to room temperature to obtain an alloy billet.

[0053] (5) The alloy blank is placed in a spark plasma sintering furnace for three stages of rapid heating and cooling heat treatment. In the first stage, the temperature is increased to 460°C at a rate of 80°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s. In the second stage, the temperature is increased to 500 to 550°C at a rate of 100°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s. In the third stage, the temperature is increased to 540°C at a rate of 120°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s to obtain an alloy sample.

[0054] (6) The alloy sample was taken out from the plasma sintering furnace, air-cooled to 170°C in air, and then placed in a heating furnace to keep warm for 5 hours. After that, the alloy sample was taken out and air-cooled to room temperature in air to obtain a hypoeutectic aluminum-silicon alloy.

[0055] The aluminum-silicon alloy prepared in this embodiment was subjected to performance tests, and the yield strength of the alloy was measured to be 410.2 MPa, the tensile strength was 500.6 MPa, the elongation was 22.8%, and the average impact energy was 33.2 J.

[0056] Example 3

[0057] The composition of the high-strength and high-toughness hypoeutectic aluminum-silicon alloy of this embodiment is shown in Table 3.

[0058] Table 3

[0059] Si Zr Fe Sr Mg margin 9.2% 0.1% 0.15% 0.015% 0.015% Al and inevitable impurities

[0060] The preparation method of the high-strength and high-toughness hypoeutectic aluminum-silicon alloy described in this embodiment specifically includes the following steps:

[0061] (1) Preheat the crucible furnace to 550°C and keep it warm for 2 hours to shorten the subsequent smelting time. According to the composition in Table 3, add the prepared single element Sr and Al-Si master alloy into the crucible furnace and heat it. Raise the temperature of the crucible furnace to 720°C and keep it warm for 20 minutes to complete the first modification treatment.

[0062] (2) Keeping the crucible furnace temperature at 720°C, add Al-Zr master alloy and refining agents (KCl) and (Na 2 SiF 6 ), while stirring the molten metal, and after keeping the temperature for 60 minutes, the secondary modification is completed. Refining agent is added to achieve the purpose of slag removal, and stirring promotes the dissolution of alloy elements.

[0063] (3) The molten alloy liquid after the secondary modification treatment is poured into a metal mold to obtain an alloy sample.

[0064] (4) The alloy sample was subjected to homogenization heat treatment at 550°C and kept at this temperature for 2 h. The alloy sample was then air-cooled to room temperature to obtain an alloy billet.

[0065] (5) The alloy blank is placed in a spark plasma sintering furnace for three stages of rapid heating and cooling heat treatment. In the first stage, the temperature is increased to 460°C at a rate of 80°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s. In the second stage, the temperature is increased to 500 to 550°C at a rate of 100°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s. In the third stage, the temperature is increased to 540°C at a rate of 120°C / s, then kept at this temperature for 2 hours, and then the alloy blank is water-quenched with running water at a flow rate of 4.5 to 5 m / s to obtain an alloy sample.

[0066] (6) The alloy sample is taken out from the plasma sintering furnace, air-cooled to 160-180°C in air, and then placed in a heating furnace to keep warm for 6 hours. Thereafter, the alloy sample is taken out and air-cooled to room temperature in air to obtain a hypoeutectic aluminum-silicon alloy.

[0067] The aluminum-silicon alloy prepared in this embodiment was subjected to performance tests, and the yield strength of the alloy was measured to be 390.2 MPa, the tensile strength was 470.7 MPa, the elongation was 20.2%, and the average impact energy was 29.7 J.

[0068] Comparative Example 1

[0069] This comparative example uses the same ingredients and the same method as Example 1 to prepare aluminum-silicon alloy, with the difference that: this comparative example uses a high-temperature box-type resistance furnace to perform staged rapid heating and cooling solution treatment, with the first stage heating rate being 20°C / min, the second stage heating rate being 30°C / min, and the third stage heating rate being 40°C / min.

[0070] The aluminum-silicon alloy prepared in this comparative example was subjected to performance tests, and the yield strength of the alloy was measured to be 320.9 MPa, the tensile strength was 378.6 MPa, the elongation was 14.2%, and the average impact energy was 18.6 J.

[0071] It can be seen from Comparative Example 1 and Example 1 that all the properties of Example 1 are better than those of Comparative Example 1. At a slower heating rate, the grains in the alloy have more time to grow, producing a coarse eutectic silicon phase, thereby causing the strength and toughness of the material to decrease.

[0072] Comparative Example 2

[0073] This comparative example uses the same ingredients and the same method as Example 1 to prepare aluminum silicon alloy, the difference is that: this comparative example does not perform staged rapid heating and cooling solution treatment, but directly raises the temperature to 540°C at a rate of 120°C / s and then keeps it warm for 6 hours.

[0074] The aluminum-silicon alloy prepared in this comparative example was subjected to performance tests, and the yield strength of the alloy was measured to be 340.9 MPa, the tensile strength was 398.6 MPa, the elongation was 15.2%, and the average impact energy was 22.6 J.

[0075] By comparing Comparative Example 2 with Example 1, it can be seen that all properties of Example 1 are better than those of Comparative Example 1. Since in Comparative Example 2, rapid heating and cooling treatment is not performed in stages, only the Si phase is refined in the alloy, and the stability of the toughness of the eutectic alloy cannot be guaranteed, which will cause the crystal structure of the aluminum-silicon alloy to change easily at the grain boundary in an industrial environment and cause cracks.

[0076] Comparative Example 3

[0077] This comparative example adopts the same method as Example 2 to prepare aluminum silicon alloy, except that: Sr is not added to the aluminum silicon alloy composition of this comparative example. The specific composition is shown in Table 4.

[0078] Table 4

[0079] Si Zr Fe Sr Mg margin 9.5% 0.2% 0.2% 0 0.02% Al and inevitable impurities

[0080] The aluminum-silicon alloy prepared in this comparative example was subjected to performance tests, and the yield strength of the alloy was measured to be 290.2 MPa, the tensile strength was 345.5 MPa, the elongation was 11.6%, and the average impact energy was 14.8 J.

[0081] By comparing with Example 2, it can be seen that the strength and toughness of the aluminum-silicon alloy sample without the addition of the Sr element is lower. This is because the presence of the Zr and Sr elements causes the eutectic Si phase to produce spheroidization, which can better couple and grow with the primary α (Al) phase to form a fine and uniform eutectic cluster; while the aluminum-silicon alloy without the addition of the Sr element has poor strength and toughness effects due to the production of coarse eutectic Si phase.

[0082] Comparative Example 4

[0083] This comparative example adopts the same method as Example 2 to prepare aluminum silicon alloy, except that: Zr is not added to the composition of the aluminum silicon alloy in this comparative example. The specific composition is shown in Table 5.

[0084] Table 5

[0085] Si Zr Fe Sr Mg margin 9.5% 0% 0.2% 0.02% 0.02% Al and inevitable impurities

[0086] The aluminum-silicon alloy prepared in this comparative example was subjected to performance tests, and the yield strength of the alloy was measured to be 345.7 MPa, the tensile strength was 412.1 MPa, the elongation was 18.4%, and the average impact energy was 24.3 J.

[0087] By comparing Comparative Example 4 with Example 2, it can be seen that the yield strength, tensile strength, elongation and average impact energy of the aluminum-silicon alloy prepared in Comparative Example 2 are inferior to those of Example 2. Since no Zr modifier is added to the aluminum-silicon alloy of Comparative Example 4, the eutectic Si phase produced in the aluminum-silicon alloy is no longer closely attached to the α(Al) growth, and columnar crystal growth begins to occur, resulting in a small amount of columnar eutectic Si phase, and the attachment effect is weakened. The refinement effect of the eutectic cluster formed is significantly weakened compared to the secondary modification, so the comprehensive performance of the alloy is reduced.

[0088] Comparative Example 5

[0089] This comparative example uses the same ingredients and the same method as Example 2 to prepare the aluminum-silicon alloy, except that: during the preparation of the aluminum-silicon alloy in this comparative example, the Zr element is added first, and then the Sr element is added.

[0090] The aluminum-silicon alloy prepared in this comparative example was subjected to performance tests, and the yield strength of the alloy was measured to be 342.3 MPa, the tensile strength was 427.3 MPa, the elongation was 14.8%, and the average impact energy was 23.5 J.

[0091] By comparing Comparative Example 5 with Example 2, it can be seen that the yield strength, tensile strength, elongation and average impact energy of the aluminum-silicon alloy prepared in Comparative Example 5 are inferior to those in Example 2. The reason is that Sr is an effective eutectic Si modifier. Compared with adding Zr first, adding Sr first can more efficiently transform the coarse lamellar eutectic Si into fine particles, thereby significantly improving the mechanical properties of the alloy, especially the plasticity, while Zr better couples the growth between the silicon phase and the primary α (Al) phase to form a small and uniform eutectic cluster. Therefore, adding Sr first can achieve the effect faster and more effectively.

[0092] In summary, the present invention optimizes the alloy composition design and combines a suitable preparation method to prepare an aluminum-silicon alloy with high strength, high toughness, and high elongation having uniform and fine eutectic clusters, thereby effectively enhancing the comprehensive mechanical properties of the aluminum-silicon alloy and expanding the application range of the aluminum-silicon alloy.

[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A high-strength and high-toughness hypoeutectic aluminum-silicon alloy, characterized in that: The hypoeutectic aluminum-silicon alloy comprises, by mass fraction, 9.2-9.8% Si, 0.1-0.3% Zr, 0.1-0.2% Fe, 0.01-0.02% Sr, 0.01-0.02% Mg, and the remainder is Al and unavoidable impurity elements.

2. A method for preparing a high-strength and high-toughness hypoeutectic aluminum-silicon alloy according to claim 1, characterized in that: The preparation method comprises the following steps: (1) After the furnace is preheated, single-element Sr and Al-Si master alloy are added according to the mass fraction, and the temperature is continuously raised to perform a modification treatment on the Al-Si master alloy; (2) keeping the heating temperature in step (1) unchanged, adding Al-Zr master alloy to the alloy after the primary modification treatment in step (1), adding a refining agent and stirring the molten metal liquid, and performing a secondary modification treatment; (3) pouring the molten metal after the secondary modification treatment in step (2) into a metal mold to obtain an alloy sample; (4) performing a homogenization heat treatment on the alloy sample obtained in step (3), and then air-cooling the alloy sample to room temperature to obtain an alloy blank; (5) subjecting the alloy blank obtained in step (4) to a rapid heating and cooling solid solution treatment in stages to obtain an alloy sample; (6) performing an aging treatment on the alloy sample obtained in step (5), and then air-cooling it to room temperature to obtain a high-strength and high-toughness hypoeutectic aluminum-silicon alloy.

3. The preparation method according to claim 2, characterized in that: In the step (1), the furnace is preheated to 550° C. and kept warm for 2 hours.

4. The preparation method according to claim 2, characterized in that: In the step (1), after adding single substance Sr and Al-Si master alloy, the temperature is raised to 700-720° C. and kept at this temperature for 20-30 minutes to complete a modification treatment.

5. The preparation method according to claim 2, characterized in that: In the step (2), after adding the Al-Zr master alloy and the refining agent, the mixture is kept warm for 50 to 60 minutes.

6. The preparation method according to claim 2, characterized in that: In the step (2), the refining agent includes potassium chloride and sodium fluorosilicate.

7. The preparation method according to claim 2, characterized in that: In the step (4), the homogenization heat treatment temperature is 500-550° C., and the insulation time is 2 hours.

8. The preparation method according to claim 2, characterized in that: In the step (5), the alloy blank is subjected to a stage-by-stage rapid heating and cooling solid solution treatment by spark plasma sintering, wherein the heating rate in the first stage is 80°C / s, the temperature is raised to 460°C, kept at this temperature for 2 hours, and then water-cooled quenching is performed; the heating rate in the second stage is 100°C / s, the temperature is raised to 500°C, kept at this temperature for 2 hours, and then water-cooled quenching is performed; the heating rate in the third stage is 120°C / s, the temperature is raised to 540°C, kept at this temperature for 2 hours, and then water-cooled quenching is performed to obtain an alloy sample.

9. The preparation method according to claim 2, characterized in that: In the step (6), the aging temperature is 160-180° C., and the insulation time is 4-6 hours.

10. The preparation method according to claim 2, characterized in that: The alloy sample obtained in step (5) is cooled to the aging temperature by air cooling, and then the alloy sample is placed in a heating furnace for heat preservation to complete the aging treatment.